Inovasi Pelayanan Jemput Bola dan Jalan Mantan dalam Pemenuhan Penerbitan KTP-el di Dinas Kependudukan dan Pencatatan Sipil Kabupaten Sikka - Cristanto Godfrid Raga; Viktor Eko Transilvalnus; Maria Silvana Mariabel Carcia (Dharma Ekonomi, 2024)
This research aims to find out how innovative pick-up and drop-off services are in fulfilling the issuance of e-KTPs at the Population and Civil Registration Service of Sikka Regency. To identify problems in this research, qualitative research methods were used. Data collection techniques in this research used interview methods, field observations and document studies. It can be concluded that in implementing the issuance of e-KTPs in Sikka Regency, DISDUKCAPIL still faces various obstacles, such as limited accessibility in rural areas, long distances, inadequate infrastructure, and minimal public knowledge about the importance of population documents. Efforts to increase the number of e-KTP issuances in Sikka Regency include the presence of the Pick Up Ball Program and Jalan Mantan (roads serving vulnerable communities) which are effective in increasing access to administrative services in remote areas and vulnerable groups through direct services at their locations. These two programs succeeded in increasing the issuance of e-KTPs thanks to a culture-based approach, intensive outreach and the role of community leaders.